Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3892/br.2014.386
|View full text |Cite
|
Sign up to set email alerts
|

Increased stathmin expression strengthens fear conditioning in epileptic rats

Abstract: Abstract. Patients with temporal lobe epilepsy have inexplicable fear attack as the aura. However, the underlying neural mechanisms of seizure-modulated fear are not clarified. Recent studies identified stathmin as one of the key controlling molecules in learning and innate fear. Stathmin binds to tubulin, inhibits microtubule assembly and promotes microtubule catastrophes. Therefore, stathmin is predicted to play a crucial role in the association of epilepsy seizures with fear conditioning. Firstly, a pilocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The highest STMN1 transcript levels in our samples were found in the amygdala, which is consistent with a previous study [ 31 ]. Moreover, we detected a significant positive correlation between STMN1 mRNA level and fear behavior, which is also in accordance with a previous report [ 42 ]. Taken together, these data suggest that STMN1 is an important determinant of fear behavior in English Springer Spaniels.…”
Section: Discussionsupporting
confidence: 93%
“…The highest STMN1 transcript levels in our samples were found in the amygdala, which is consistent with a previous study [ 31 ]. Moreover, we detected a significant positive correlation between STMN1 mRNA level and fear behavior, which is also in accordance with a previous report [ 42 ]. Taken together, these data suggest that STMN1 is an important determinant of fear behavior in English Springer Spaniels.…”
Section: Discussionsupporting
confidence: 93%
“…More specifically, 15 epileptic rats and 5 control rats for western blotting; 5 epileptic rats and 5 control rats for RT-qPCR and 5 epileptic rats and 5 control rats for ChIP assay (Table I). The epilepsy model was established using lithium chloride (LiCl)/Pilocarpine (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) as previously described (13). Rats were injected intraperitoneally with LiCl (127 mg/kg) and then with pilocarpine (30 mg/kg) 18 to 24 h following the first injection.…”
Section: Methodsmentioning
confidence: 99%
“…Stathmin is probably regulated by a basic fear because it is highly expressed under normal conditions. Studies from knockout animals found reduced contextual fear memory and impaired dentate gyrus LTP in stathmin−/− mice, indicating that stathmin was a positive regulator of fear memory (Shumyatsky et al, 2002 ; Uchida et al, 2014 ; Zhang et al, 2015 ). In addition, abilities to properly assess a threat, provide parental care, and interact socially as adults are deficient in stathmin knockout animals (Martel et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%